ENGLISH TEACHERS’ PERCEPTIONS OF STUDENT EVALUATION OF TEACHING IN AN INDONESIAN UNIVERSITY - Rentauli Maria Silalahi (Association for the Teaching of English as a Foreign Language in Indonesia (TEFLIN), 2021)
Student evaluation of teaching (SET) has been proven to improve teachers’ teaching practices and students’ learning experiences despite being used commonly for accountability purposes. Indonesian teachers’ perceptions of SET, however, remain largely unexplored. This qualitative study therefore investigated how four Indonesian university teachers perceived SET, how SET impacted their teaching practices and what roles they believed the university should play in implementing SET properly. The participants taught English to undergraduate students in an Indonesian private university. Data were collected using semi-structured interviews and analysed using qualitative methods. The teachers perceived SET positively, had made conscious changes to improve their teaching practices and students’ learning, and believed the institution had facilitated teachers in meeting students’ needs, especially during the campus closure due to the COVID-19 pandemic, which led to a transition to online learning. The institution where the participants taught implemented SET only for formative or improvement purposes. Using SET for such purposes is important as it is more likely to cause teachers less pressure and anxiety. Hence, teachers are willing to act upon the student feedback. Meanwhile, using SET for accountability purposes may create extra work for teachers and make them feel manipulated and untrusted.